Supporting Early Reading Develovment Through Kipintar Media: a Classroom-Based Study in Indonesian Primary Education - Shinta Wijaya Wijaya; Alif Hasanah; Ewinestri Hanidar Nur Afifi; Anindya Syam Choudhury (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
Early reading proficiency is a fundamental literacy skill that supports students' subsequent academic development. This study aimed to examine the application of KIPINTAR media in early reading instruction for third-grade students at SDIT Salafiyah Syafi'iyah, Sorong Regency. A non-experimental quantitative approach with a descriptive observational design was employed involving seven third-grade students. Data were collected using observation sheets for early reading ability and student engagement, along with validation instruments for the research instrument and the KIPINTAR media. The validation results indicated that the research instrument achieved an average validity score of 81.67% (valid), while the KIPINTAR media obtained a feasibility score of 95.00% (very feasible) and a practicality score of 86.87% (very practical). Observations of students' early reading performance demonstrated a consistent improvement across four learning sessions, with the average class achievement increasing from 66.07% at the first meeting to 70.83%, 83.33%, and 91.07% in subsequent meetings, resulting in an overall average of 77.83%. In addition, students demonstrated a high level of engagement throughout the learning process, with an average enthusiasm score of 3.68 out of 4. These findings suggest that the implementation of KIPINTAR media effectively facilitates progressive improvement in early reading skills while fostering active student participation. The media supports letter recognition, word formation, and simple word reading through interactive learning activities, indicating its potential as an effective instructional medium for strengthening early literacy instruction in elementary schools.